2018
DOI: 10.4291/wjgp.v9.i2.37
|View full text |Cite
|
Sign up to set email alerts
|

Acinar cell injury induced by inadequate unfolded protein response in acute pancreatitis

Abstract: Acute pancreatitis (AP) is an inflammatory disorder of pancreatic tissue initiated in injured acinar cells. Severe AP remains a significant challenge due to the lack of effective treatment. The widely-accepted autodigestion theory of AP is now facing challenges, since inhibiting protease activation has negligible effectiveness for AP treatment despite numerous efforts. Furthermore, accumulating evidence supports a new concept that malfunction of a self-protective mechanism, the unfolded protein response (UPR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…ERS is implicated as a cause of inflammation in many disorders and reported to be associated with intestinal barrier dysfunction in inflammatory bowel diseases (19). Accumulating evidence supports that ERS in the pancreas is a driving force behind the pathogenesis of ANP (20), but how ERS in the intestine works in ANP is rarely explored. One study (21) suggested that ERS was induced in the ileal epithelia during 3% sodium taurocholate-induced pancreatitis, indicated by an irregular, dilated endoplasmic reticulum and Bip upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…ERS is implicated as a cause of inflammation in many disorders and reported to be associated with intestinal barrier dysfunction in inflammatory bowel diseases (19). Accumulating evidence supports that ERS in the pancreas is a driving force behind the pathogenesis of ANP (20), but how ERS in the intestine works in ANP is rarely explored. One study (21) suggested that ERS was induced in the ileal epithelia during 3% sodium taurocholate-induced pancreatitis, indicated by an irregular, dilated endoplasmic reticulum and Bip upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies targeting ER stress regulatory molecules have shed light on their effects on pancreatic function and disease pathology and have uncovered a balance between protective (eg, IRE1/XBP1s) and pathologic (PERK/ATF4/CHOP) UPR in pancreatic physiology and disease. 5 , 9 , 11 , 28 The present study shows marked up-regulation and/or dysregulation of pathologic cellular pathways including PERK, CHOP, and c-jun N-terminal kinase with loss of AT-1; however, the CP observed in Ela-Cre AT-1 -/- appeared to be relatively mild to moderate, suggesting a capability of acinar cells to adapt to chronic ER stress when the protective IRE1/XBP1s UPR is intact. Interestingly, it was shown previously that AT-1 expression may be downstream of IRE1/XBP1s, suggesting that AT-1 also may play a role in the protective ER stress response 21 ; this is supported further by the finding that AT-1 expression increases at the initiation of pancreatitis, but is down-regulated as the disease progresses.…”
Section: Discussionmentioning
confidence: 52%
“…The UPR is a well-studied set of cellular pathways designed to monitor and respond to the accumulation of proteins within the endoplasmic reticulum (ER) lumen. 2 , 4 , 5 There are 3 protein sensors, in brief: inositol-requiring enzyme 1 (IRE1), which produces a spliced variant of the transcription factor X-box binding protein 1 (XBP1s), activating transcription factor (ATF)6, and protein kinase R-like ER kinase (PERK), which phosphorylates elongation initiation factor 2α (eIF2α). Both XBP1s and ATF6 act to expand the ER and enhance protein folding capabilities, while eIF2α phosphorylation inhibits cap-dependent protein translation, reducing ER input.…”
mentioning
confidence: 99%
“…Endoplasmic reticulum stress can also trigger necroptosis. According to reports, many unfolded or misfolded proteins accumulate in the endoplasmic reticulum, when acinar cells are challenged by injury or other stresses 35,36 . In our research, we innovatively demonstrated that rSAA3 could promote CCK‐induced acinar cell necroptosis, but whether this is a direct or indirect effect remains unknown.…”
Section: Discussionmentioning
confidence: 75%